EU prohibition of discrimination on grounds of nationality in the context of Polish civil procedure - AGNIESZKA KASTELIK-SMAZA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2025)
The prohibition of discrimination on grounds of nationality is one of the most important principles of EU law. At the same time it is a fundamental right which can be invoked directly before the courts and administrative organs of the Member States. The study analyses EU provisions on non-discrimination on grounds of nationality, their content and evolution. It also considers these regulations in the context of Polish civil procedure as they has had a significant impact on the application and wording of certain provisions of the Polish Code of Civil Procedure, being the subject to interpretation in conformity with EU law, the basis for preliminary references to the Court of Justice, and eventually legislative amendments due to the conflict with EU law.